Analisis Makna Pada Puisi “Sajak-Sajak Empat Seuntai” Karya Sapardi Djoko Damono Menggunakan Pendekatan Semiotik - Caca Hidayat (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
Poetry is a literary work which contains expressions of the author poured into written form with implied meaning so the readers can interpret the results of the written work freely. This study used qualitative method with semiotic approach such as: 1) to describe the meaning of the poems 2) to know the number of icons, 3) to know the number of indexes, 4) to know the number of symbols. The results showed (1) this poem has a deep meaning about the closeness of a human being with his creator, so that at first he was far away but after trying to keep getting closer he felt a calmness, which he had never felt before, (2) there was a choice of diction that used icons, indexes, and symbols written by Sapardi Djoko Damono in expressing the meaning of the poem